A longitudinal study among young adults into the predictive effect of perceived efficacy of behavioural strategies and the moderating role of drinking motives on use of protective behavioural strategies - González Ponce, Bella M. (2022)
Introduction: Although protective behavioural strategies (PBS) have shown to be effective in minimising alcohol-related negative consequences, research on the explanatory factors of their use is very scarce. Perceived efficacy has been demonstrated to be one of the most relevant explanatory factors in the use of health-related protective behaviours. The present study prospectively examines the relationship between the perceived efficacy of PBS in reducing alcohol-related negative consequences and the use of PBS in a community-based sample of young adults. In addition, the moderating role of drinking motives in this relationship is also examined. Methods: Prospective design with a baseline assessment and a 2-month follow up. Using a targeted sampling procedure, 339 young adults were recruited from the community [mean age: 21.1 (SD = 2.21); female = 50.7%] and completed questionnaires to measure perceived efficacy of PBS and drinking motives at baseline and PBS use at follow up. Results: Perceived efficacy of PBS at baseline was positively associated with PBS use at follow up, and these relationships were weaker as social, enhancement and coping motives scores increased. Discussion and Conclusions: Our findings support the need to include the perceived efficacy of PBS to reduce alcohol-related negative consequences in future interventions aimed at promoting PBS use. Moreover, these interventions should be personalised according to the initial levels of participants' drinking motives, incorporating elements that allow for neutralising their negative effects on PBS use (e.g. training in coping skills for those with strong coping motives).